Pembentukan Kampung Tangguh Bencana Syurdori Distrik Supiori Timur - Dina Ruslanjari; Retnadi Heru Jatmiko; Sigit Sulistiyo (Yayasan REDI Tiga Monas, 2024)
Supiori Regency is one of the areas in Papua Province which is included in the frontier, remote, and underdeveloped region in the Pacific Ocean, which is quite vulnerable to experiencing a series of natural events that have the potential to become a disaster for the local population. The disaster threat index in Supiori Regency includes tsunamis, earthquakes and extreme waves and abrasion (GEA). A total of approximately 20 settlements in Syurdori Village (part of the East Supiori District) were affected by a tsunami with a tsunami height of 7 meters that occurred in 1996 which resulted in several houses being damaged by tsunami waves. The purpose of this article is to examine the process and benefits of establishing a disaster resilient village (Kamtana), the process of increasing community preparedness and the process of creating a participatory evacuation route map in Syurdori Village, East Supiori District, Supiori Regency, Papua Province. The research method used was qualitative, with primary data collection techniques in the form of focus group discussions (FGDs). The sampling technique used in selecting the research location used a purposive sampling method based on the condition of the vulnerability of Syurdori Village to various disasters, especially floods, extreme waves and abrasion, earthquakes and tsunamis. The results of this study are the implementation process of establishing a Disaster Resilient Village, increasing community preparedness and conducting a participatory mapping process related to determining evacuation routes in Syurdori Village, Papua Province.